Genetic Dissection of Presynaptic and Postsynaptic BDNF-TrkB Signaling in Synaptic Efficacy of CA3-CA1 Synapses - Pei-Yi Lin; Ege T. Kavalali; Lisa M. Monteggia (Cell Reports, 2018)
Summary: Brain-derived neurotrophic factor (BDNF) and its high-affinity receptor, tropomyosin receptor kinase B (TrkB), regulate long-term potentiation (LTP) in the hippocampus, although the sites of BDNF-TrkB receptors in this process are controversial. We used a viral-mediated approach to delete BDNF or TrkB specifically in CA1 and CA3 regions of the Schaffer collateral pathway. Deletion of BDNF in CA3 or CA1 revealed that presynaptic BDNF is involved in LTP induction, while postsynaptic BDNF contributes to LTP maintenance. Similarly, loss of presynaptic or postsynaptic TrkB receptors leads to distinct LTP deficits, with presynaptic TrkB required to maintain LTP, while postsynaptic TrkB is essential for LTP formation. In addition, loss of TrkB in CA3 significantly diminishes release probability, uncovering a role for presynaptic TrkB receptors in basal neurotransmission. Taken together, this direct comparison of presynaptic and postsynaptic BDNF-TrkB reveals insight into BDNF release and TrkB activation sites in hippocampal LTP. : Lin et al. directly compare a role for presynaptic and postsynaptic BDNF and TrkB receptors in hippocampal LTP. They find that LTP induction is mediated by anterograde BDNF-TrkB signaling, while both anterograde and retrograde BDNF-TrkB signaling persists presynaptically and postsynaptically for LTP maintenance. Keywords: BDNF, TrkB, hippocampus, synaptic plasticity, LTP, presynaptic, postsynaptic